Observation of Chok Anan mango flower using scanning electron microscope. - Ding, Phebe; K.B., Darduri; Z., Wahab (2007)
Flowering and the fruit set are the most critical of all events occuring after establishment of a tree crop.A fundamental understanding of mango flowering in the tropics is essential to efficiently utilize cropping management systems which could extend both the flowering and crop production seasons. However, the information and appreciation of the floral biology of this popular fruit species is still lacking. Therefore, the objective of this work is to observe the anatomy of Chok Anan mango flowers using scanning electron microscope. The flower of Chok Anan is a monoecius flower where it has male and hermaphrodite flowers in the same panicle. The fruit will develop from hermaphrodite flower while the male flower will contribute the pollen when pollination occured. The Chok Anan mango flowers contain five sepals and five petals and arranged in a whorl. There were not much differences in the structure of sepals an petals consists of ground parenchyma tissue with laticcifier and idioblast cells, starch granules and vascular bundle tissues. Trichomes present in both sepals and petals. The male flower has the same structure as the hermaphrodite flower except that it does not has carpel, that is the ovary, style and stigma.